Digital constraints and opportunities. Reorganizing teaching procedures in time of emergency - Cabeleira, João (2021)
In the view of the emergency determined by the Corona Pandemic, higher education institutions were forced to review their practices both in terms of institutional organization as well as the approaches and methodologies applied to the teaching/learning process. A change dictated by the urgency and that implied the revision of an entire mental and relational framework questioning daily practices taken for granted.